Master and commander the far side of the world - Weir, Peter 1944-; Collee, John; Smith, Lee; Davies, Iva; Gordon, Christopher; Tognetti, Richard; Crowe, Russell 1964-; Bettany, Paul 1971-; Darcy, James; Woodall, Edward; Larkin, Chris 1967-; Pirkis, Max; et al.
During the Napoleonic Wars, a British frigate, the HMS Surprise, and the larger French warship, Acheron, stalk each other off of the coast of South America. Lucky Jack, as he is referred to by his crew, is well regarded by his men, who trust him implicitly, even after the first devastating battle and an apparent personal vendetta against the French captain. The ship's surgeon balances the violence of his chosen life with the quiet demeanor of the scientist. He is the captain's friend and confidant, the two frequently playing violin and cello duets together